Smart Culture Management: Theoretical Aspects - Milkintas, Rytis (Socialiniai tyrimai, 2020)
The aim of the research is the investigation of the essential theoretical aspects of smart culture management. The article formulates the theoretical construct of smart culture management by combining cultural management and management concepts, closely linking cultural management with the implementation of cultural policy and seeing the specifics of smart cultural management. Qualitative analysis was performed of theoretical sources of foreign countries and Lithuania. Also, a comparative analysis of different concepts was carried out, highlighting similarities and differences of concepts (in order to discern correlations between them). Five groups of cultural management concepts are distinguished: cultural management as specific management in art and culture; cultural management as a phenomenon, process reflecting the formation and implementation of cultural policy; cultural management as an institution management; cultural management as a profession and academic discipline; cultural management as leadership-based management. Theoretical analysis of the phenomenon of smartness in cultural management allowed us to distinguish six dimensions of smartness: strategic, creative development, harmonization of interests in the cultural sector, empowered cultural sector parties, the harmony of intellectual and technological capital, the culture of shared value creation. Exploring the urban cultural field situation, using a model that reflects the 6 dimensions of smart culture management and 18 qualities of a smart social system, will highlight the strengths and weaknesses of the cultural field. By analyzing the weaknesses, the researchers will be able to make recommendations on how to improve the current situation. Improving the cultural field at the local level will significantly increase the quality of cultural services provided to the population. In future research, it is planned to apply the theoretical model of smart culture management to the analysis of situation analysis in the selected city. Analysis based on this theoretical model can also be performed at the state level, thus providing a comprehensive view of the cultural field situation.